2015
DOI: 10.1177/1049731515610637
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic OQ-45 Outcome Differences

Abstract: Purpose: The purpose of this exploratory study was to determine whether Native American clients seen at a University Counseling Center had different treatment outcomes than did Caucasian clients according to the Outcome Questionnaire-45 (OQ) given at the first and final sessions. Methods: Participants included self-identified 21 Native American and 105 Caucasian clients who received services over the past 7 years and who had OQ-45 scores. Results: American Indian total scores on the OQ-45 were not that much di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There have been cross-cultural comparisons of the OQ-45 (Lambert et al, 2006), and it has been translated into Spanish (Iraurgi & Penas, 2021). A comparison study with AI and White university students found similar scores on the OQ-45 pre- and post-treatment (Limb et al, 2017); however, this study did not examine the psychometric validity of the measure. To our knowledge, there are no measurement invariance studies of the OQ-45.…”
Section: Summary Of Review Findingsmentioning
confidence: 92%
“…There have been cross-cultural comparisons of the OQ-45 (Lambert et al, 2006), and it has been translated into Spanish (Iraurgi & Penas, 2021). A comparison study with AI and White university students found similar scores on the OQ-45 pre- and post-treatment (Limb et al, 2017); however, this study did not examine the psychometric validity of the measure. To our knowledge, there are no measurement invariance studies of the OQ-45.…”
Section: Summary Of Review Findingsmentioning
confidence: 92%
“…Although there have been slight increases in receiving counseling services among communities of color (e.g., Latinx and Asian), a significant decrease was noted regarding received counseling services among Black community members, with 17% decreasing to 14.8% between 2020 and 2021 (Centers for Disease Control and Prevention [CDC], 2022). However, research data on counseling outcomes for communities of color is limited, given that research has mainly explored counseling outcomes with Asian, Latinx, and American Indian communities, which produced varying counseling outcomes for these communities (Kim et al., 2016; Limb et al., 2017. With these points in mind, it is essential for counselors to be well‐trained in being able to understand white supremacy's impacts on minoritized communities, as well as affirming counseling skills to help support communities of color in their unique lived experiences.…”
Section: Who Does White Supremacy In Counselor Education Hurt?mentioning
confidence: 99%